2010
DOI: 10.1371/journal.pone.0011221
|View full text |Cite
|
Sign up to set email alerts
|

Location-Specific Responses to Thermal Stress in Larvae of the Reef-Building Coral Montastraea faveolata

Abstract: BackgroundThe potential to adapt to a changing climate depends in part upon the standing genetic variation present in wild populations. In corals, the dispersive larval phase is particularly vulnerable to the effects of environmental stress. Larval survival and response to stress during dispersal and settlement will play a key role in the persistence of coral populations.Methodology/Principal FindingsTo test the hypothesis that larval transcription profiles reflect location-specific responses to thermal stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
96
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 92 publications
5
96
0
Order By: Relevance
“…A. millepora populations in the central and southern GBR have been shown to be genetically distinct, at least partly because regular dispersal between inshore reefs in the two regions is inhibited by an oceanographic front (van Oppen et al 2011). In a study of Caribbean populations of Montastraea faveolata that were not genetically differentiated, evidence of local adaptation was nevertheless observed in aposymbiotic larval cohorts from different thermal regions, based on differences in patterns of gene expression and developmental malformation under elevated temperature (Polato et al 2010). Variation in the thermal responses of larvae raised from different crosses of A. millepora from the same population provides evidence of a mechanism by which local population adaptation could be facilitated (Meyer et al 2009).…”
Section: Variation In Thermal Tolerance Amongmentioning
confidence: 99%
See 1 more Smart Citation
“…A. millepora populations in the central and southern GBR have been shown to be genetically distinct, at least partly because regular dispersal between inshore reefs in the two regions is inhibited by an oceanographic front (van Oppen et al 2011). In a study of Caribbean populations of Montastraea faveolata that were not genetically differentiated, evidence of local adaptation was nevertheless observed in aposymbiotic larval cohorts from different thermal regions, based on differences in patterns of gene expression and developmental malformation under elevated temperature (Polato et al 2010). Variation in the thermal responses of larvae raised from different crosses of A. millepora from the same population provides evidence of a mechanism by which local population adaptation could be facilitated (Meyer et al 2009).…”
Section: Variation In Thermal Tolerance Amongmentioning
confidence: 99%
“…However, restrictions to gene flow are expected to have enhanced adaptive divergence among populations across large spatial scales (van Oppen and Gates 2006), and, indeed, regional differences in thermal limits observed following short periods of experimental acclimation suggest that some populations have adapted to their local thermal environments (Coles et al 1976, Ulstrup et al 2006). Yet, strong evidence of local thermal adaptation in coral and Symbiodinium partners is limited due to the difficulty of controlling for long-term acclimatization effects in adult corals sourced from different environments (but see Polato et al 2010, Howells et al 2012. Thus, the extent of local adaptation in coral and Symbiodinium populations remains unclear, as well as any constraints that such adaptation may place on the potential for acclimatization to gradual long-term changes in temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Rodriguez-Lanetty et al 2009, Voolstra et. al 2009, Polato et al 2010, Portune et al 2010. However, most of these studies examined the effects of elevated temperature on tropical or subtropical scleractinian corals, while data on octocorals and temperate corals are lacking (but see Zeevi-Ben-Yosef & Benayahu 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is worth mentioning that only the expression of four genes were assessed, and that manganese superoxide dismutate was found to be significantly heritable in one population, with a zinc metalloprotease heritable in the other [54]. Casting a wider net with the use of cDNA microarray interrogating 1,310 unigenes, Polato et al [55] compared the heat stress response of Montastraea faveolata larvae from Mexico and Florida sites of origin. In spite of the presence of gene gene flow between the two sites assessed, the study revealed origin-specific gene expression patterns [55], giving evidence for a host response to differing environmental exposure.…”
Section: Evidence For the Heritability Of Stress Response In Coralmentioning
confidence: 99%
“…Casting a wider net with the use of cDNA microarray interrogating 1,310 unigenes, Polato et al [55] compared the heat stress response of Montastraea faveolata larvae from Mexico and Florida sites of origin. In spite of the presence of gene gene flow between the two sites assessed, the study revealed origin-specific gene expression patterns [55], giving evidence for a host response to differing environmental exposure. For further evidence for heritable parental influence, we look to the recent work of Polato et al [56], in which parental crosses between Acropora palmata of known microsatellite genotypes we performed for the specific purpose of creating two pools of genotypically distinct larval offspring.…”
Section: Evidence For the Heritability Of Stress Response In Coralmentioning
confidence: 99%